1990
DOI: 10.2307/2135681
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Knowledge and Sexual Behavior Among High School Students

Abstract: Data from the 1989 Secondary School Student Health Risk Survey indicate that 54 percent of all high school students in the United States had had some form of HIV/AIDS education in school. Responses to a questionnaire on HIV/AIDS knowledge show that nearly all students knew the two main modes of HIV transmission--intravenous drug use and sexual intercourse. Students who had been taught about HIV and AIDS in school gave correct answers to questions about the virus more often than those who had not received instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
2
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 5 publications
3
38
2
1
Order By: Relevance
“…In addition, 23.3% of the students who ever had sex reported that they never used a condom when they had sexual intercourse. 9 IV drug use has also been reported in surveys of youth, but the extent and nature of illicit drug-injection behavior among adolescents has not been well studied. Surveys of IV drug use in relatively small or geographically limited populations of adolescents have shown considerable variation in rates, ranging from 0.1 to 6.3%.…”
Section: Inrodudionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 23.3% of the students who ever had sex reported that they never used a condom when they had sexual intercourse. 9 IV drug use has also been reported in surveys of youth, but the extent and nature of illicit drug-injection behavior among adolescents has not been well studied. Surveys of IV drug use in relatively small or geographically limited populations of adolescents have shown considerable variation in rates, ranging from 0.1 to 6.3%.…”
Section: Inrodudionmentioning
confidence: 99%
“…The sampling frame, which consisted of all US public-and private-school students in grades 9 by the questionnaire: demographic characteristics, HIV instruction, HIV attitudes, HIV knowledge, and HIV-related risk behaviors. Variables used in the current analysis are descnbed in more detail below.…”
Section: Medods Stuy Populationmentioning
confidence: 99%
“…Several recent studies have investigated the extent to which adolescents in the United States engage in behaviors that place them at risk for HIV infection. [1][2][3][4][5] Although a few studies have tried to assess changes in these behaviors over time, their findings have been limited. "…”
mentioning
confidence: 99%
“…Many beliefs related to AIDS put adolescents at risk for exposure to the HIV virus. For example, 12% of a national sample believed that birth control pills provide some protection against HIV infection, and 23% believed that one can tell whether a person has AIDS by looking at them (Anderson et al, 1990). In addition, Tatum (1988) contended that adolescents often associate HIV/AIDS with gays and bisexuals ("the gay disease") , which frequently leads to homophobia (fear and mistrust of gays and lesbians).…”
Section: Sex Education Programsmentioning
confidence: 99%